1999
DOI: 10.1074/jbc.274.6.3355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genes Encoding Known and Novel Human Mast Cell Tryptases on Chromosome 16p13.3

Abstract: Tryptases are serine proteases implicated in asthma and are very highly expressed in human mast cells. They fall into two groups, ␣ and ␤. Although several related tryptase mRNAs are known, it is unclear which if any are transcripts of separate haploid genes. The studies described here investigated the nature and number of human tryptases and sought possibly novel members of the family. To this end, two human bacterial artificial chromosome (BAC) clones containing tryptase genes were identified and mapped to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
161
1
6

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(182 citation statements)
references
References 36 publications
(35 reference statements)
12
161
1
6
Order By: Relevance
“…They are 95-99% identical and are encoded by 2 adjacent genes on human chromosome 16p13.3 (20). Their murine equivalents are mouse MC protease 6 (mMCP-6) (21) and mMCP-7 (22).…”
mentioning
confidence: 99%
“…They are 95-99% identical and are encoded by 2 adjacent genes on human chromosome 16p13.3 (20). Their murine equivalents are mouse MC protease 6 (mMCP-6) (21) and mMCP-7 (22).…”
mentioning
confidence: 99%
“…All populations of MCs examined to date store in their secretory granules various combinations of carboxypeptidase A, chymases, and tryptases ionically bound to serglycin proteoglycans that contain either heparin or highly sulfated chondroitin glycosaminoglycans. Human MCs express at least five distinct tryptases, and the cDNAs and genes have been isolated that encode human tryptases ␣, ␤I, ␤II, and ␤III, as well as a less homologous transmembrane tryptase (5)(6)(7)(8)(9)(10). Mapping and sequencing analysis of the region of human chromosome 16, where these genes reside, has revealed the presence of additional genes in the family (9,11), but it remains to be determined whether or not any of these genes encode enzymatically active proteases.…”
mentioning
confidence: 99%
“…Several in vitro studies have identified multiple substrates for tryptase, including neuropeptides, fibrinogen, stromelysin, prourokinase, prothrombin, and protease-activated receptor-2 (3-6). Human chromosome 16 encodes several homologous tryptase genes, designated tryptase ␣, ␤, and ␥ (7,8). The ␤-tryptases share greater than 99% sequence identity, with tryptase ␤I and ␤II differing by a single N-glycosylation site.…”
mentioning
confidence: 99%